If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 71 + -2x = 16x + 19 Reorder the terms: 71 + -2x = 19 + 16x Solving 71 + -2x = 19 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 71 + -2x + -16x = 19 + 16x + -16x Combine like terms: -2x + -16x = -18x 71 + -18x = 19 + 16x + -16x Combine like terms: 16x + -16x = 0 71 + -18x = 19 + 0 71 + -18x = 19 Add '-71' to each side of the equation. 71 + -71 + -18x = 19 + -71 Combine like terms: 71 + -71 = 0 0 + -18x = 19 + -71 -18x = 19 + -71 Combine like terms: 19 + -71 = -52 -18x = -52 Divide each side by '-18'. x = 2.888888889 Simplifying x = 2.888888889
| 12-7x=52-35x | | 5(3d+2)+15=4(2d+5)+7d+5 | | 0.5+2.8=3.64 | | 9(c+2)-11=5(2c+3)-2c | | 14x=8x+24 | | 18x+106=45 | | 5x+14=-42-9x | | 11d-9=15d+3 | | 12x-5x=7 | | -7+t=24 | | 98-4x=3x+14 | | -19-3x=9-10x | | 59-3x=9x+23 | | 3(x-4)=x+24 | | 2(2b+1)+5=3(2b+1)-b | | 5x+11=-106-8x | | 60k=54 | | 6x+7=4x-5 | | 6x+21=16x-89 | | 4y-20=8 | | 10x-6x=24 | | 8-3x-x=12 | | 60-5x=10x+15 | | t-(-4)=17 | | 8x-19=3x-1 | | 2(3x+6)=5(2x-4)-4x | | 15+4r=231 | | (7y+7)+(3y-17)= | | x+(-8)=22 | | 4x+30=8x | | 4x=2x+14 | | 1.05=-7m |